Analyzing Creativity in the Light of Social Practice Theory - Città, Giuseppe; Gentile, Manuel; Augello, Agnese; Ottaviano, Simona; Allegra, Mario; Dignum, Frank (Frontiers in Psychology, 2019)
In this work, starting from the social practice theory, we identified two kinds of creativity. A situational creativity that takes place when a social practice is performed and a creativity of habit that concerns the agents’ capacity of evoking different practices from habit. To test this hypothesis the Torrance Test of Creative Thinking (Verbal Form A) was analyzed in the light of praxeology.